2014
DOI: 10.1021/jf404175t
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of 4-Hydroxyderricin and Xanthoangelol on Lipopolysaccharide-Induced Inflammatory Responses in RAW264 Macrophages

Abstract: The Japanese herb, Ashitaba (Angelica keiskei Koidzumi), contains two prenylated chalcones, 4-hydroxyderricin and xanthoangelol, which are considered to be the major active compounds of Ashitaba. However, their effects on inflammatory responses are poorly understood. In the present study, we investigated the effects and underlying molecular mechanisms of 4-hydroxyderricin and xanthoangelol on lipopolysaccharide (LPS)-induced inflammatory responses in RAW264 mouse macrophages. LPS-mediated production of nitric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…When tested against Chang liver cells, compounds 7, 10, 11, 14, 24, 26, 28-31, 33, 34, and 38 showed inhibitory effects on NO almost equal to the reference compound glyzyrrhizin [3,17]. In another study, compounds 1 and 2 were also shown to suppress the production of NO in RAW264 macrophages, with negligible effects on cellular function [32]. The authors noted that prenylated chalcones were more effective in suppressing NO formation, with 2 being more potent than 1.…”
Section: Oxidative Stress Relief and Anti-inflammatory Activitymentioning
confidence: 95%
See 3 more Smart Citations
“…When tested against Chang liver cells, compounds 7, 10, 11, 14, 24, 26, 28-31, 33, 34, and 38 showed inhibitory effects on NO almost equal to the reference compound glyzyrrhizin [3,17]. In another study, compounds 1 and 2 were also shown to suppress the production of NO in RAW264 macrophages, with negligible effects on cellular function [32]. The authors noted that prenylated chalcones were more effective in suppressing NO formation, with 2 being more potent than 1.…”
Section: Oxidative Stress Relief and Anti-inflammatory Activitymentioning
confidence: 95%
“…Ashitaba extract and compound 2 were shown to inhibit inflammation induced by TNF-α in male kwl ICR mice [35]. Another study determined that isolated compounds 1 and 2 had similar TNF-α suppressing effects in RAW264 macrophages [32], and compound 5 induced suppression in porcine aortic endothelial cells [33]. In RAW246.7 macrophages, the n-hexane ashitaba extract had anti-inflammatory activity resulting from the downregulation of NF-κB-dependent gene products [34].…”
Section: Oxidative Stress Relief and Anti-inflammatory Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Xanthoangelol, a major constituent of AKE, exhibits antioxidative and anti-inflammatory properties. 16,17 AKE was suggested to improve the pathological abnormalities associated with ALD and proposed as a possible new therapeutic agent for the treatment of ALD. However, the hepatoprotective effects of AKE have not been well established.…”
Section: Introductionmentioning
confidence: 99%